Individual properties of personality as criterion of choice of style of game of tennis players - O.G. Shalar; E.A. Strikalenko; A.N. Ivaschenko (Physical Education of Students)
The features of different styles of game are considered in table tennis and intercommunication with individual psychological properties of personality of tennis players is shown. Characterological and intellectual indexes of sportswomen of high class, which come forward in club championship of Ukraine on table tennis, is studied. 15 sportswomen of high class, among which a 1 master of sport of international class, 7 masters of sport and 7 candidates in masters of sport, took part in research. It is set that the excitable (100 %) is inherent the tennis players of attacking style of game, hyperthymic, emotive and ecstatic (80 %) type of accentuation and brightly expressed persistence. Hyperthymic prevails for the tennis players of the combined style of game, emotive, cyclothymic and demonstrative (100 %), anxious and excitative (80 %) type of accentuation. Tennis players-defenders have a sense to hyperthymic, emotive and to ecstatic (100 %), anxious, to the cyclothymic (80 %) type of accentuation. Tennis players of the combined and protective style of game are in 80 % cases have a high level of intellectual capabilities. However more expressed motivation to success is for the tennis players of attacking style of game (60 %).